BETTER INTEGRATED INSTRUCTION OF GEOMETRY AND ALGEBRA IN PRIMARY EDUCATION - Glavche, Metodi; Anevska, Katerina; Malčeski, Risto (Matematichki Bilten, 2016)
The integrated teaching of mathematics is important for the development of the students from every aspect. Practice shows that integrated knowledge improves the quality of thinking and at the same time enables the students to acquire permanent and applicable knowledge. Although there are declarative efforts for acquiring integrated knowledge, there is lack of inter-subject and intra-subject integration. This paper scrutinizes how elementary geometry knowledge can be used to improve integrated instruction. We are going to show how to come up with formulas for some sums of numbers by using areas of squares and rectangles. The latter is especially important since these formulas are presented to the students either in a dogmatic way, or through mathematic induction, which is incomprehensible for most students of this age.